2022
DOI: 10.3389/fimmu.2022.1031185
|View full text |Cite
|
Sign up to set email alerts
|

Genetic engineering of pigs for xenotransplantation to overcome immune rejection and physiological incompatibilities: The first clinical steps

Abstract: Xenotransplantation has the potential to solve the shortfall of human organ donors. Genetically modified pigs have been considered as potential animal donors for human xenotransplantation and have been widely used in preclinical research. The genetic modifications aim to prevent the major species-specific barriers, which include humoral and cellular immune responses, and physiological incompatibilities such as complement and coagulation dysfunctions. Genetically modified pigs can be created by deleting several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 152 publications
0
6
0
Order By: Relevance
“…Removal of SLAs from donor pigs has been considered to avoid immune rejection of the xenograft. 60,61 However, SLA deletion can render the pig at risk for infectious complications. 62 Alternatively, site-specific SLA mutations are recommended to avoid the reactivity with anti-HLA antibodies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Removal of SLAs from donor pigs has been considered to avoid immune rejection of the xenograft. 60,61 However, SLA deletion can render the pig at risk for infectious complications. 62 Alternatively, site-specific SLA mutations are recommended to avoid the reactivity with anti-HLA antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Removal of SLAs from donor pigs has been considered to avoid immune rejection of the xenograft 60,61 . However, SLA deletion can render the pig at risk for infectious complications 62 .…”
Section: Discussionmentioning
confidence: 99%
“…Xenotransplantion has been notorious for very high rates of failures when it was first suggested. The discovery of the Gal epitope and the finding of the concordant and discordant species was a serious advancement in the field (Lei et al, 2022; Sykes & Sachs, 2022). Recently, Griffith et al reported genetically modified porcine‐to‐human cardiac xenotransplantation.…”
Section: Discussionmentioning
confidence: 99%
“…(An excellent review has been provided by others). 91 The innate immune cellular response can be inhibited by certain genetic modifications in the donor pig, for example, expression of human CD47 and/or HLA molecules (HLA-E and/or G) that suppress macrophage and NK cell activation, respectively. 92-96…”
Section: The Innate Cellular Immune Responsementioning
confidence: 99%
“…Innate immune cells, for example, macrophages, monocytes, and natural killer (NK) cells, also play significant roles 90 which to date have been insufficiently studied and are less well‐defined. (An excellent review has been provided by others) 91 . The innate immune cellular response can be inhibited by certain genetic modifications in the donor pig, for example, expression of human CD47 and/or HLA molecules (HLA‐E and/or G) that suppress macrophage and NK cell activation, respectively 92–96 …”
Section: The Mechanism Of Amr In Xenotransplantationmentioning
confidence: 99%